2021
DOI: 10.1039/d0cy02333g
|View full text |Cite
|
Sign up to set email alerts
|

Ni/NiO heterostructures encapsulated in oxygen-doped graphene as multifunctional electrocatalysts for the HER, UOR and HMF oxidation reaction

Abstract: A controlled scalable arc-discharge method was developed to produce metal/metal oxide nanoparticles encapsulated in graphene as excellent catalysts for multiple reactions, including HER, UOR, and the HMF oxidation reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…Also, NiSe was converted into a core–shell structure, covered by a nickel oxide/hydroxide shell, proving to have good catalytic activity and superior stability for water splitting and methanol oxidation [93] . Wang et al [94] . recently reported Ni/NiO nanoparticles encapsulated in oxygen‐doped graphene as multifunctional electrocatalysts for hydrogen evolution, urea oxidation, and HMF‐EOR.…”
Section: Electrochemical and Photocatalytic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, NiSe was converted into a core–shell structure, covered by a nickel oxide/hydroxide shell, proving to have good catalytic activity and superior stability for water splitting and methanol oxidation [93] . Wang et al [94] . recently reported Ni/NiO nanoparticles encapsulated in oxygen‐doped graphene as multifunctional electrocatalysts for hydrogen evolution, urea oxidation, and HMF‐EOR.…”
Section: Electrochemical and Photocatalytic Methodsmentioning
confidence: 99%
“…Also, NiSe was converted into a core-shell structure, covered by a nickel oxide/hydroxide shell, proving to have good catalytic activity and superior stability for water splitting and methanol oxidation. [93] Wang et al [94] recently reported Ni/NiO nanoparticles encapsulated in oxygen-doped graphene as multifunctional electrocatalysts for hydrogen evolution, urea oxidation, and HMF-EOR. The oxygengraphene shell plays a fundamental role in increasing the stability and activity of Ni/NiO since protects the Ni-based catalyst from the alkaline electrolyte and provides active sites for the reaction.…”
Section: Electrochemical Oxidationmentioning
confidence: 99%
“…[74] The yield of FDCA was close to 100 %, and the faradaic efficiency of HMF conversion was 99.4 %. A variety of Ni-based electrocatalysts with excellent properties have been prepared, such as trimetallic NiCoFe-LDHs, [75] ultrathin Ni(OH) 2 nanosheets modified with amorphous Cu(OH) 2 islands, [76] sulfurmodulated nickel/carbon composites (SÀ Ni@C), [77] P-doped NiB x (NiB x À Py), [78] Ni/NiO heterostructures encapsulated with oxygendoped grapheme, [79] and V 2 O 3 -doped Ni 3 N. [80] In addition, some Ni-based catalysts are bifunctional electrocatalysts, which catalyze the oxidation of HMF as an anode material, and efficiently promote HER as a cathode material. A three-dimensional NiP nanoparticle array on nickel foam (Ni 2 P NPA/NF) can efficiently electrocatalyze the HMF-to-FDCA oxidation and the preparation of H 2 .…”
Section: Direct Strategymentioning
confidence: 99%
“…In addition, Iwona et al [ 88 ] deposited Ni on reduced graphene oxide, which has a cauliflower-like structure with a well-developed surface morphology, thereby enhancing the catalytic activity of Ni for HER by water. A new catalyst of Ni/NiO nanoparticles encapsulated in graphene layers was prepared by Wang et al [ 89 ] using an arc discharge method at 30 V and 100 A. The catalyst showed superior HER activity based on synergy and achieved a low overpotential of 112 mV at a current density of 20 mA/cm 2 in 1 M KOH solution, and the HER activity equivalent to that of the rare metal Pt.…”
Section: Graphene-based Her Electrocatalystsmentioning
confidence: 99%